The role of student-generated externalizations in strategic multimedia learning and how current (web-)technology fails to support learner engagement. Issue 7 (2nd October 2016) - Ploetzner, Rolf; Fillisch, Benjamin; Gewald, Patrick-André; Ruf, Tatjana
Abstract : In two studies, we investigated how learning strategies can support learning from multimedia. In the first study, 112 students learned from a web-based learning environment. On the basis of a strategy, one group of students took typewritten notes. The second group of students wrote a summary. Producing typewritten notes did not benefit learning any more than writing a summary. In the second study, 100 students learned the same subject matter from print. On the basis of a strategy, the first group produced written notes, the second group highlighted, wrote notes, and produced sketches. The third group wrote a summary. The students who highlighted, wrote notes, and produced sketches outperformed the other students. The students who produced written notes only did not learn more successfully than those who wrote a summary. The results suggest that externalizations in general and sketches in particular may play an important role in multimedia learning.